The Housing Market: Marketing Strategies Used by SME’s in the UK and China. - Wells, Lydia (2011)
I intend to investigate how a SME can survive the UK recession through the use of marketing techniques, focusing specifically on the housing industry through a case study approach of an estate agency firm. My study will place particular emphasis on the topic of Relationship marketing. Moreover I shall compare the similarities and differences of the marketing strategies of this independent service SME to a larger, multiple branch estate agency which is part of a larger firm. Furthermore, there will also be a discussion of the Chinese house market and the concept of guanxi, defining this concept and comparing it to Relationship marketing. I will also be exploring if there appears to be any link between the two and if there is any situation in which both concepts can be applicable to a service oriented SME.